WAKAF TUNAI DALAM KAJIAN FIQH MUAMALAH - Nasrul Amanu (Jurnal At Taajir, 2020)
The issue of cash waqf is not really a new case in the study of fiqh. Historically, cash waqf basically included in the khilafiyah. The legal disagreement occurs as a result of culture and understanding of the legal community is still struggling in the region of fixed asset waqf. Thereare several answers as well as a legal opinion to be used as proof to some madzhabscholars, one of which is the opinion of Imam Hanafi that allow cash as waqf endowments on the basis of Istihsan bi al-’Urfi.The basic argument of the Hanafi is the hadeeth narrated by Abdullah bin Mas’ud, may Allah be pleased. While, Imam Malik also allow the base diwakafkan quality goods. Beside those arguments, Imam Shafi’i does not allow cash waqf and argue that the cash waqf does not immortal (can disappear). Theseare the law of several fuqaha answers to this problem. While in Indonesia, legally justify the cash waqf with the issuance of Undang-Undang No. 41 Tahun 2004 about Endowments and Peraturan Pemerintah (Government Regulation)No. 42 Tahun 2006 about The Implementation of Undang-Undang No. 41Tahun2004 which the Regulation Legislation can provide legal certainty on the applicationand implementation cash waqf in Indonesia.